2011
DOI: 10.25011/cim.v34i1.15104
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between arterial and venous sampling of circulating hormones, substrates and peptides in severe obesity

Abstract: Purpose: Severely obese patients are being encountered more frequently in clinical practice. Factors implicated in the relationship between obesity and cardiovascular disease may be measured from a blood sample obtained through arterial access in a cardiology setting, such as during cardiac catheterization or heart surgery. The comparability of a given sample site (arterial vs. venous) with regards to blood parameters is yet to be established. Methods: Fifteen severely obese patients undergoing bariatric surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Recent studies suggest that compared to arterialized blood, venous blood provides lower concentrations of glucagonlike peptide-1 (38) as well as lower glucose concentrations and higher insulin sensitivity (39). Although limited evidence in patient populations suggests that fasting ghrelin concentrations are comparable between venous and arterialized blood (40,41), direct comparisons of acylated ghrelin and total PYY between arterialized and venous blood after exercise has not been investigated. Nevertheless, the findings of the present study are relevant to the wider exercise and appetite regulation literature where blood sampling from an antecubital vein is commonplace for quantifying appetiteregulatory hormone concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that compared to arterialized blood, venous blood provides lower concentrations of glucagonlike peptide-1 (38) as well as lower glucose concentrations and higher insulin sensitivity (39). Although limited evidence in patient populations suggests that fasting ghrelin concentrations are comparable between venous and arterialized blood (40,41), direct comparisons of acylated ghrelin and total PYY between arterialized and venous blood after exercise has not been investigated. Nevertheless, the findings of the present study are relevant to the wider exercise and appetite regulation literature where blood sampling from an antecubital vein is commonplace for quantifying appetiteregulatory hormone concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Biomarker levels in our study were measured in arterial blood; these levels may differ from venous levels. However, Martin et al showed that arterial and venous levels of hsCRP and NTproBNP did not differ [ 35 ]. Also, levels of NTproBNP, hsCRP, CysC and MPO were measured using an in-house ELISA method instead of clinically standardised assays.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial, central venous, peripheral venous, or capillary blood samples were analyzed on the Cobas E801 analyzer using the Elecsys proBNP II method (Roche Diagnostics). Different types of blood sampling presumably lead to comparable NT-proBNP values [ 35 , 36 ]. The measuring range for the used method is 5–35,000 ng/l.…”
Section: Methodsmentioning
confidence: 99%